A Meta-Synthesis of Disability Research in Western Africa. (February 2023) - Blasko, Alyssa M.; Morin, Kristi L.; Bauer, Kathleen; Johnson, Kelsey M.; Enriquez, Grace B.; Hunsicker, Lindsey E.; Tasik, Emily J.; Renz, Theodore E.
Most disability research is conducted in high-income countries, despite much of the world's population living in low- and middle-income countries. Given the flexible nature of qualitative research, studies using this methodology have the potential to provide important insights into how disability is perceived across the globe. The aim of the current study was to synthesize the results of disability research in Western Africa to elucidate prominent themes and identify methodological and participant characteristics. Secondary purposes were to evaluate the quality of included studies. A total of 223 studies were included in this meta-synthesis. Findings reveal a diversity of disability-related themes and a need to increase transparency in reporting qualitative research. Implications and suggestions for future research are discussed.